CSR authenticity and consumers´ attitudes in the context of food waste : the case study of Too Good To Go - Silva, Beatriz Azevedo e (2021)
In a society that is becoming increasingly demanding with the corporate world, it is important to discern which direction companies must take in order to generate more positive attitudes among consumers in what concerns CSR endeavours. Indeed, consumers’ perceptions towards CSR are showing more and more inconsistencies, but the concept of authenticity might help mitigating the contradictions. This study focuses on understanding if having CSR deeply embedded in the business affects consumers’ perceptions about the authenticity of companies’ CSR actions. This is achieved through individual interviews with consumers of a company that has its roots in socially responsible behaviour. Too Good To Go created a possible solution to fight food waste and turned it into its core business. This dissertation develops a case study based on how this company conducts its business and how this innovative approach affects authenticity perceptions and consumer behaviour, consequently. Results show that consumers tend to be more sceptical, instead of considering companies’ actions authentic. Even though companies that were born with socially responsible purposes have better chances of being perceived as authentic, the corporate world has lost consumers’ trust and it needs to redirect the way it conducts business in the long-run. Insights from consumers resulted in some implications regarding CSR and suggestions on how to improve CSR authenticity perceptions.